2015
DOI: 10.1021/acs.energyfuels.5b01894
|View full text |Cite
|
Sign up to set email alerts
|

Gum Formation in Gasoline and Its Blends: A Review

Abstract: Gasoline is a volatile mixture of hydrocarbons that is used in spark-ignition (SI) engines. It is a complex mixture composed of olefinic, paraffinic, naphthenic, and aromatic hydrocarbons (C 4 −C 12 ), among other substances in a smaller concentration. In several countries, such as Brazil, ethanol is used pure as a renewable fuel for SI engines, especially in flex fuel engines, and/or an additive to improve the octane number of gasoline. During storage, some classes of hydrocarbons in gasoline blends, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 80 publications
1
52
0
1
Order By: Relevance
“…Gum refers to the resinous, non-volatile, high molecular weight polymeric material formed in fuels in storage or when exposed to high temperature conditions during combustion in engines [1]. Gum formation and inhibition in refined petroleum products such as gasoline, diesel and aviation fuel has been extensively studied as a result of its impact on product storability and engine performance but similar studies on gas condensates are scarce [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gum refers to the resinous, non-volatile, high molecular weight polymeric material formed in fuels in storage or when exposed to high temperature conditions during combustion in engines [1]. Gum formation and inhibition in refined petroleum products such as gasoline, diesel and aviation fuel has been extensively studied as a result of its impact on product storability and engine performance but similar studies on gas condensates are scarce [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Gum formation is believed to be a free-radical chain polymerization process mediated by peroxy radicals [1,3]. The presence of trace heavy metals such as iron, copper, cobalt and manganese is known to increase the rate of gum formation because heavy metals facilitate the production of peroxides by catalyzing the decomposition of hydroperoxide [1]. Resins and asphaltenes although present in low concentration in condensates, increase the potential for gum formation in condensates due to their large polycondensed heteroaromatic structures.…”
Section: Introductionmentioning
confidence: 99%
“…(4), (5), or (6)). The formation of high molar mass species with long carbon chain results of these three reactions (A'reff, 2011;De la Puente and Sedran, 2004;Heneghan and Zabarnick, 1994;Pradelle et al, 2015a;Roan and Boehman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Literature showed that the stability of hydrocarbons decreases in the order of paraffins, naphthenes, isoparaffins, aromatics, monoolefins (in particular, cyclic and branched olefins), aromatic olefins and diolefins, especially conjugated compounds (De la Puente and Sedran, 2004;Gilbert, 2004;Nagpal et al, 1994Nagpal et al, , 1995aNagpal et al, , 1995bPasa, 2006, 2007;Pradelle et al, 2015a;Rahimi et al, 1998;Teixeira et al, 2007). The oxidation rate is proportional to the concentration of atmospheric oxygen absorbed by the fuel (Schwartz et al, 1968a(Schwartz et al, , 1968bShatalov and Seregin, 2009;Stavinoha et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation